A Randomized and Blinded Study for the Treatment of Glenohumeral Internal Rotation Range of Motion Restriction: The Prone-Passive Stretching Technique - Dave Hammons; John W. McChesney; Michael Curtin; Ronald Pfeiffer; Keith Thiede (Bowling Green State University, 2015)
A Randomized and Blinded Study for the Treatment of Glenohumeral Internal Rotation Range of Motion Restriction: The Prone-Passive Stretching Technique Background: Prior research has focused on specific interventions to reduce the symptoms of glenohumeral internal rotation deficit (GIRD) and posterior glenohumeral (GH) tightness; however, clinicians often utilize a prone stretching technique instead for which a lack of evidence exists to support the use of. Hypothesis: Improvements in GH Internal rotation (IR) range of motion (ROM) will be greater in a group of overhead athletes using a prone-passive stretching technique than for overhead athletes using a cross-body stretching technique. Design: Randomized and blinded comparative research study Methods: 34 asymptomatic overhead athletes exhibiting ≥ 10° of GH IR deficit randomly received either 12 prone-passive (n=17) or cross-body (n=17) stretching treatments for the deficit over a consecutive 28 day period. Measures of IR and external rotation (ER) for both the dominant and non-dominant shoulders were taken with a modified digital inclinometer before and after participants underwent 12 treatments over a consecutive 28-day period in either the prone-passive or cross-body group. Results: Analysis revealed increased dominant shoulder IR ROM and total motion, whereas IR deficit decreased for both groups, but no group differences. Gain scores for the prone-passive and cross-body respectively: IR ROM (13.23° ± 7.78°, 8.47° ± 8.71°), IR deficit (-12.64° ± 11.49°, -9.13 ± 8.33°), and total motion (14.81° ± 11.27°, 9.97° ± 11.99°). Conclusion: The prone-passive stretching technique is as effective as the cross-body technique at improving IR ROM, IR deficit, and total motion in the shoulder joint in participants with IR deficit. Clinical Relevance: Accounting for IR deficits in the overhead athlete shoulder is effectively managed through both clinician-assisted and self-stretching techniques. Clinicians treating overhead athletes with greater limitations in IR ROM may find the prone-passive technique advantageous when compared to the cross-body technique.